Pengaruh Media Sosial (Instagram) terhadap Keputusan Pembelian di Toko Hijacu Hijab di Kota Palopo - Leni Nurhalisah; Deswi Natalia Dwi; Rahmania Rahmania; Iin Safitri Pakidi; Rudianto Rudianto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the effect of social media marketing on Instagram on purchasing decisions at Hijab Hijacu store with quantitative approach. The research was conducted on 50 followers of Instagram @hijacuhijab account who had made online purchasing as a sample. Data were obtained using a questionnaire that has been online distributed and measured with a Likert scale. After analyzing with simple regression, it shows that ownership of social media has a positive effect on purchasing decisions.